Preparation of Laser-Modified Ti-15Mo Surfaces With Multiphase Calcium Phosphate Coatings - Santos, Marcio Luiz dos; Almeida Filho, Edson de [UNESP]; Silva, Vagner Pereira; Tranquilin, Ricardo L.; Carnietto, Jessica da Silva [UNESP]; Guastaldi, Antonio C. [UNESP]; Silva Perreira, Regina Mara; Riccardi, Carla dos Santos [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2020)
Multiphasic bioceramic scaffolds has been enhanced for dental and orthopedic applications. In this perspective, the laser surface texturing of metallic surfaces combined to bioactive calcium phosphate coatings have shown to be promising and economically feasible for biomaterial clinical applications. Ti-15Mo alloy samples were irradiated by pulsed Yb: YAG laser beam. The formation of HA and other calcium phosphates phases by biomimetic method should occur in the presence of Ca2+, PO43-, Mg2+, HCO3-, K+ and Na+. The modified surfaces were submitted to thermal treatment at 380 and 580 degrees C. The results showed the processes of fusion and fast solidification from the laser beam irradiation, inducing the formation of stoichiometric alpha-Ti, TiO2 and non-stoichiometric titanium oxides, Ti3O and Ti6O with different oxide percentages depending on applied fluency (fluency of 0.023, 0.033, 0.040 and 0.048 J/mm(2)). The morphological and physicochemical properties have indicated the formation of a multiphase bioceramic coatings. It was observed the formation of amorphous calcium phosphate (ACP), octacalcium phosphate (OCP), and magnesium phosphate (Mg-3(PO4)(2)) phases at 380 degrees C, whereas beta-TCP (tricalcium phosphate), OCP, and substituted beta-TCP with Ca2,589Mg0,41(PO4)(2) were obtained at 580 degrees C. Therefore, the multiphasic bioceramic modified Ti-15Mo surface could enhance osteointegration for bone regeneration.
Keywords: Ti-15Mo alloy; biomimetic coatings; calcium phosphates; laser ablation